Filtros ambientais, interações bióticas e variabilidade climática afetando o crescimento, recrutamento e mortalidade de árvores em florestas de ecótono na Ilha de Maracá, Roraima - Silva, Williamar Rodrigues (2020)
Effects of climate change on the structure, growth and mortality of trees in tropical forests under different environmental conditions need to be better elucidated throughout the Brazilian Amazon. Spatio-temporal monitoring studies of tree demography have been crucial to understand how the structure and composition of tropical forest species respond to global climate variations. In this sense, this study aimed to determine the effect of environmental conditions and climate variation on the vital rates (growth, recruitment and mortality) of arboreal individuals from ecotonal forests in the central-west of Roraima between the years 2016-2020. The vital rates of this period were correlated in the light of independent variables: (i) structural (diameter, density of individuals, height, richness and composition of species), (ii) environmental (texture and soil fertility, topography) and (iii) (cumulative water deficit = CWD, sea surface temperature = SST). Both the dependent variables (vital rates) and the structural and environmental independent variables were derived from 129 plots (10 mx 50 m; 6.45 ha) installed in a hydro-edaphic gradient characterized by ecotone forests (ombrophilic + seasonal forests) dispersed in the east of Maracá Island, state of Roraima. The climate independent variables were obtained freely from databases available on the world wide web. Annual demographic census surveys were carried out on 129 plots, where all tree individuals (trees + palms; stem diameter ≥ 10cm) were measured and identified taxonomically. To reach the general objective of the study, the investigation fulfilled four specific objectives that represent individual chapters of the work: (i) floristic composition; (ii) forest structure (density and height of trees); (iii) community structuring (species richness and composition) and (iv) forest dynamics (vital rates). The results of chapter I revealed that the floristic composition of the plots used as samples is characterized by 42 botanical families and 140 species and morpho-species. Peltogyne gracilipes Ducke (Leguminosae), Pradosia surinamensis (Eyma) T. D. Penn. (Sapotaceae) and Ecclinusa guianensis Eyma (Sapotaceae) were the species with the highest importance index (~ 25%), corresponding to more than 36% dominance. Chapter II demonstrated that the organic matter of the soil and the sum of the bases explained 16% of the variation in the density of the trees, while the density of the trees and the sum of the extractable bases explained 13% of the variation in the average height of the trees. Chapter III indicated that the species richness and composition responded to the same environmental factors: altitude, clay content and the sum of micronutrients in the soil. These variables affected species composition directly and indirectly, through the abundance of P. gracilipes. In particular, the latter suppressed species richness, regardless of soil conditions. These results support the hypothesis that abiotic filters and biotic interactions shape the studied tree communities and that P. gracilipes can be considered an indicator species of hydro-edaphic conditions, but it should also be seen as a propeller of the structure of the tree community. Finally, Chapter IV indicated that the forest dynamics varied annually according to the number of stems and the above-ground living biomass (AGB) taking into account the period between January/2016 to January/2020 in the 129 permanent plots. The number of living individuals was reduced by 4.6%, from 3041 (2016) to 2902 (2020) considering the three arboreal groups (Palms, Trees and P. gracilipes) defined for the studied ecotone forest. The total AGB, considering the three tree groups, decreased from 295.76 Mg ha-1 to 287.97 Mg-1 (-7.79 Mg ha-1; -2.63%). This reduction was due to a high mortality rate in the period (1.94%) associated with low recruitment (R = 0.77%). The rate of total AGB change of the three tree groups was conditioned by the sum of the micronutrients (Fe, Zn, Mn, B, Cu; mg kg-1). When the tree groups were analyzed separately, it was observed that each responded to different environmental factors. The content of phosphorus (P) affected the rate of change of AGB of the Palmeiras while the clay content and the sum of nutrients affected the group of Trees. The total rate of change of AGB of tree groups was not statistically conditioned by the climatic descriptors (CWD, SST), although the graphical response indicates a delay time (1-2 years) in the forest's response to climatic stresses, especially in those of dry years. The general results of the investigation improve our understanding of the dynamics (growth, recruitment and mortality) of ecotone forests in northern Brazilian Amazon, and can be used as an information base for the construction of public policies aimed at mitigating the negative effects of global warming in forest areas in the Amazon.